2009
DOI: 10.1161/circresaha.109.196592
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 2 Mediates Redox-Sensitive Endothelial Cell Proliferation and Angiogenesis by Thrombin via Rac1 and NADPH Oxidase 2

Abstract: Abstract-Cyclic nucleotide phosphodiesterases (PDEs) control the levels of the second messengers cAMP and cGMP in many cell types including endothelial cells. Although PDE2 has the unique property to be activated by cGMP but to hydrolyze cAMP, its role in endothelial function is only poorly understood. Reactive oxygen species (ROS) have been recognized as signaling molecules controlling many endothelial functions. We thus investigated whether PDE2 would link to ROS generation and proliferative responses in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
64
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 42 publications
8
64
1
Order By: Relevance
“…These results serve to confirm the emerging idea that PDE2A is a key proinflammatory enzyme that enhances the cellular and humoral inflammation associated with common forms of tissue injury (14,41,44,52).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These results serve to confirm the emerging idea that PDE2A is a key proinflammatory enzyme that enhances the cellular and humoral inflammation associated with common forms of tissue injury (14,41,44,52).…”
Section: Discussionsupporting
confidence: 76%
“…cAMP is a key defensive signaling molecule in the injured lung, opposing LPS-and ROS-mediated cell death, preserving endothelial and epithelial intercellular junctions, and enhancing edema clearance (16,21,23,26,28,38). For example, increased PDE2A expression in human umbilical vein endothelium was recently reported to increase thrombin-induced NADPH oxidase activity and ROS production by a loss of cAMP inhibition of rac1 activity (14). cAMP also serves as a critical regulator of lung macrophage function suppressing cytokine and chemokine production as well as iNOS expression (40).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF activates Rac1 via vav-2 (Garrett et al, 2007) and activation of Rac1 is involved in the hypoxia-induced production of angiogenesis-promoting factors (Xue et al, 2006). Thrombin-induced angiogenesis requires Rac1 and NADPH oxidase 2 (Diebold et al, 2009). Inhibition of Rac1 reduces VEGF-induced tyrosine phosphorylation of VEGFR-2 (Ushio- Fukai et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…101 In particular, Rac1 and Rac2 are involved in the activation of NOX1, NOX2, and NOX3. [101][102][103] This function of Rac, first demonstrated in neutrophils and other phagocytic cells and later expanded to non-phagocytic cells, 104 is important in both physiological 105 and pathophysiological [106][107][108] settings. Rac1 has been shown to associate with many enzymes necessary for maintaining redox homeostasis in cells.…”
Section: Redox Regulation By Racmentioning
confidence: 99%
“…In contrast to the vast amount of literature documenting Rac-mediated ROS production, [101][102][103][104][105][106][107][108] relatively few studies have investigated the role of ROS/RNS in regulating Rac activity. Nagase et al have demonstrated ROS-mediated activation of Rac1 in rat cardiomyocytes.…”
Section: Redox Regulation Of Racmentioning
confidence: 99%